Revealing the effect of impacted canines on the adjacent teeth. A three dimensional study using CBCT - Ebrahim S Alshawy; Shaul H Kolarkodi (Wolters Kluwer Medknow Publications, 2023)
Objective: The current cross-sectional study aimed to assess the relationship between impacted maxillary canines and their effect on root resorption of neighboring teeth using cone-beam computed tomography (CBCT). Materials and Methods: The study evaluated the effect of 24 impacted maxillary canines on the adjacent tooth roots. We used a CBCT to evaluate the position and size of the dental follicle of impacted maxillary canines and the severity of root resorption on adjacent teeth. We used a t-test to compare the significant differences between the width of the dental follicle and the severity of root resorption. The inter- and intra-rater agreements were assessed. Results: A number of 12 impacted canines had resorbed the roots of adjacent teeth. Lateral incisors were most affected (83.3%), followed by central incisors (16.7%). Mild root resorption was found in 10 cases, while severe resorption was found in two cases. We found no relation between the size of the dental follicle and the degree of root resorption. The inter- and intra-rater agreements were high. Conclusion: In cases with maxillary impacted canines, special consideration should be directed to the roots of the maxillary lateral incisors. Our findings could not confirm any relationship between the size of the dental follicle width of the maxillary impacted canines and the degree of root resorption of the adjacent incisors. More studies are needed to assess the proximity and path of eruption of impacted maxillary canines and their effect on the neighboring teeth.